The Essence of the Prohibition of Tender Rigging from a Business Competition Law Perspective - Tedjokusumo, Dave David; Kagramanto, Lucianus Budi; Prasetyawati, Endang; Nasution, Krisnadi (Batulis Civil Law Review, 2024)
Introduction: The government has made efforts to ensure that existing business competition legal regulations can accommodate the broad legal needs of society, but in reality, in everyday life, legal problems are still often encountered. One of the fundamental legal issues related to business competition in Indonesia is regarding government procurement of goods/services. There are many practices of bid rigging in the process of procuring government goods/services to determine the winner in a tender. Tender conspiracy cases often occur in Indonesia, therefore everything related to tender conspiracy must be carefully scrutinized. Purposes of the Research: The aim of this research is to analyze and discover the nature of the prohibition on bid rigging from a business competition law perspective.Methods of the Research: The research method used is normative juridical. Descriptive and argumentative techniques must be used in carrying out the analysis.Results of the Research: The essence of the prohibition on bid rigging from a business competition law perspective can actually be observed in Article 22 of Law no. 5/1999, Per. KPPU No. 2/2010, and Constitutional Court Decision Number 85/PUU-XIV/2016. This prohibition aims to not give rise to unhealthy business competition, so that the aim of holding tenders can be achieved properly to provide equal opportunities to business actors in offering competitive prices and quality, which in the end will result in the lowest price with the best quality.